THE INFLUENCE OF MOLYBDENUM DISULPHIDE-FRICTION MODIFIER (FM) ADDITIVE INCREMENT ON THE FRICTION AND WEAR PREVENTION BEHAVIOUR OF HVI 60 BASE OIL - Muhammad Hanifuddin; Nofrijon Sofyan (Testing Center for Oil and Gas LEMIGAS, 2015)
Friction will always be found in a mechanical system. It is therefore necessary to minimize friction, so it becomes a more effi cient use of energy. This paper discusses the infl uence of MoS2 friction modifier (FM) additive in the form of powder with two different mesh sizes, i.e. 90 nm and 1.5 um, on the friction and wear characteristic of HVI 60 base oil. The variation of MoS2 were 0,05%; 0,1%; 0,5% weight whereas MoS2 1.5 um were 0,05%; 0,1%; 0,5%; 1% and 2% weight. MoS2 additive 90 nm was mixed with base oil and stirred with magnetic stirrer for 60 minutes at 50oC and homogenized in an ultrasonic homogenizer for 1 hour. For the MoS2 1.5 um, the additive was mixed with base oil and stirred with magnetic stirrer for 60 minutes at 75oC without using an ultrasonic homogenizer. Friction and wear characteristics of these mixtures were tested using four-ball and SRV test-rig. The wear scars were analyzed by using a scanning electron microscope (SEM). The results of the tests showed that the addition of 0.1% weight MoS2 additive, both in 90 nm and 1.5 um, resulted in an optimum increase in friction and wear characteristic of 23% and 11%, respectively. Observation on the wear scar showed that adhesive and abrasive wear mechanisms were involved in the wear process. The results of this research could be applied in the production of lubricating oils that can improve engine performance. Keywords: additive, friction, wear, molybdenum disulfi de, four-ball